13. TWENTY-FOUR-HOUR HOLTER ELECTROCARDIOGRAPHY FINDINGS IN GENERAL INTERNAL MEDICINE DEPARTMENT 1, TRANSPORT HOSPITAL (2019–2024) (Vietnam Journal of Community Medicine, 2026)
Study objectives: • Survey of characteristics of the patients monitored by 24-hour Holter electrocardiogram.2. Evaluation of the recorded arrhythmias and heart rate variability.Methods: Cross-sectional descriptive study, conducted on 659 inpatients and outpatients at the Department of Internal Medicine No. 1 of Transport Hospital (Hanoi) from 2019 to September 2024. Patients were monitored by 24-hour Holter electrocardiogram machines and data were analyzed using SPSS software.Results:- Characteristics of the study group: Male patients accounted for 59.5%, female 40.5%; mean age 47.62 ± 23.22 years. 35.2% of all patients had at least one diagnosed disease.- Recorded arrhythmias: Sinus tachycardia is the most common (77%), ventricular extrasystoles (53%), atrial fibrillation (6.9%). Severe ventricular arrhythmias (Lown grade ≥ 3) tend to increase in the age group ≥ 60 years.- Heart rate variability: SDNN, mean NN and pNN50 indices decrease significantly with age and the severity of comorbidities such as hypertension, diabetes, heart failure.Conclusion: 24-hour Holter electrocardiogram is a useful tool in detecting and evaluating arrhythmias. This study provides additional data on the role of Holter electrocardiogram in the diagnosis and prognosis of cardiovascular diseases in Vietnam.
Keywords: Holter electrocardiogram; arrhythmia; heart rate variability.